COMMUNITY ENGAGEMENT IN THE BALIGE PEOPLE'S MARKET REVITALIZATION PROGRAM - Murti Ningrum Siahaan; R. Sally Marisa Sihombing (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The revitalization of the people's market is one of the programs of the trade policy with the aim that the people's market can be more optimal, the negative perception of the people's market disappears and empowers the people's market community so that the people's market is able to fulfill its strategic functions. However, the implementation of market revitalization in Balige has not been able to create such a market. This shows that there are obstacles in community engagement so that the development results are colored by conflicts that are rejected by community groups, especially traders. This study aims to describe in detail community engagement in the revitalization of the Balige people's market. The research method used is descriptive research with a qualitative approach. Data collection was carried out by interview, observation, and documentation techniques. The data was obtained and analyzed qualitatively with the community engagement theory approach proposed by Vargas (2014) including genuine community involvement: building community strength, building trust, horizontal relationships and empowerment through co-leadership and participatory processes. The results of the study show the dimension of genuine community involvement: building community strength has not used a bottom-up approach with policies that only utilize land assets and balerong cultural heritage. Building trust between the government and traders and among traders has not been achieved with a commitment to involve traders only by carrying out six socialization sessions and two hearings and a lack of intervention to meet the needs of traders. Horizontal relations have not been implemented because a cooperative culture has not been formed due to mistrust and mutual relations that are also not carried out. Empowerment of traders is not carried out where traders are not involved in the participatory process in decision-making and in important task forces. Community Engagement has not been optimally implemented as a decision-making strategy in the Balige people's market revitalization program.